2015
DOI: 10.2147/ijn.s89783
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanoparticle treatment ameliorates peritonitis-induced diaphragm dysfunction

Abstract: The severe inflammation observed during sepsis is thought to cause diaphragm dysfunction, which is associated with poor patient prognosis. Cerium oxide (CeO 2 ) nanoparticles have been posited to exhibit anti-inflammatory and antioxidative activities suggesting that these particles may be of potential use for the treatment of inflammatory disorders. To investigate this possibility, Sprague Dawley rats were randomly assigned to the following groups: sham control, CeO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have confirmed that CeO2 nanoparticles can act as superoxide dismutase mimics [4] and catalase mimics [5] and can reduce pulmonary hypertension [6] and reduce hypoxia-induced oxidative stress [7] as well as inhibiting cyclophosphamide-induced apoptosis [8]. In the study of peritonitis, CeO2 nanoparticles have been reported to reduce peritonitis-related SIRS [2], and other studies have found that CeO2 nanoparticles can improve diaphragmatic dysfunction caused by peritonitis [9]. In addition, green tea polyphenols, as the main ingredients of antioxidants, are well known for their antioxidant, anti-inflammatory, anticancer, anticardiolipin, antimicrobial, antihyperglycemic, and antiobesity properties [10].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have confirmed that CeO2 nanoparticles can act as superoxide dismutase mimics [4] and catalase mimics [5] and can reduce pulmonary hypertension [6] and reduce hypoxia-induced oxidative stress [7] as well as inhibiting cyclophosphamide-induced apoptosis [8]. In the study of peritonitis, CeO2 nanoparticles have been reported to reduce peritonitis-related SIRS [2], and other studies have found that CeO2 nanoparticles can improve diaphragmatic dysfunction caused by peritonitis [9]. In addition, green tea polyphenols, as the main ingredients of antioxidants, are well known for their antioxidant, anti-inflammatory, anticancer, anticardiolipin, antimicrobial, antihyperglycemic, and antiobesity properties [10].…”
Section: Introductionmentioning
confidence: 97%
“…The ceria nanozyme significantly improved survival and protected the liver from sepsis-induced injury. Similarly, other studies have also shown that ceria nanozymes can reduce functional sepsis-induced injury to the liver and diaphragm through their antioxidant and anti-inflammatory activities [ 89 , 90 ].…”
Section: Nanomaterials For Rons Eliminationmentioning
confidence: 92%
“… [ 72 ] TD-NT High polymer materials / PAMPs/DAMPs Decreased inflammatory cytokines levels and improved tissue damage in sepsis mice Captured DAMPs and PAMPs simultaneously / [ 74 ] Nanomaterials for RONS Elimination CeNPs Ceria / Antioxidant enzyme Decreased RONS and inflammatory cytokines levels; improved survival rate and protected liver from sepsis-induced injury / Large doses of ceria oxide nanoparticles may induce liver injury and oxidative stress. [ 88 ] / Improved diaphragmatic inflammation and function / [ 89 ] / Inhibited inflammatory cytokines secretion; alleviated hepatic damage; increased survival rate / [ 90 ] CZ-NPs Cerium and Zirconia / Antioxidant enzyme Exhibited a decreased RONS levels and an improvement of tissues damage in sepsis mice Exhibiting a stronger antioxidant activity Large doses of ceria oxide nanoparticles may induce liver injury and oxidative stress. [ 91 ] 6-AHA-CeNPs 6-AHA-modified cerium oxide / Antioxidant enzyme Exerted antioxidant and anti-inflammatory capacity; increased survival rates; improved lung and liver tissues damage Increasing stability and bioavailability of ceria nanozyme; decreasing toxicity Large doses of ceria oxide nanoparticles may induce liver injury and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…15 a). The antioxidant effect of conventional CeO 2 nanoparticles is achieved with the chemical transformation of Ce 3+ to Ce 4+ , which partially attenuates oxide stress and proinflammatory responses in mice with sepsis [ 231 , 232 ]. However, the low reprocessing of Ce 3+ limits the therapeutic efficiency of CeO 2 nanoparticles and enhances their toxicity due to the large doses used.…”
Section: Nanotherapeutic Platforms For Sepsis Treatment Through Targementioning
confidence: 99%